Advertising Media: A Code Analysis of Food and Beverage Advertisement Compilations on YouTube - Hutabarat, Novra Melisa (Journal of English Language and Education, 2026)
The use of linguistic coding in advertising discourse constitutes an important communicative strategy that reflects the diversity of language structures employed in marketing practices. The deliberate integration of multiple languages in advertisements serves not only to attract audience attention but also to support the preservation and visibility of regional languages through contemporary media platforms. This study aims to investigate instances of code-switching and code-mixing in food and beverage advertisement compilation videos uploaded by Rofif Satria on  the YouTube Satria Channel. The research adopts a qualitative approach with a descriptive design. Data were collected through systematic observation and note-taking procedures. Each advertisement video was carefully examined, and all verbal and written elements were transcribed. Instances of code-switching and code-mixing were then identified, classified, and documented. The collected data were organized according to their linguistic forms and categorized based on the types of code-switching and code-mixing present. The findings indicate that code-switching and code-mixing occur frequently in advertising discourse, encompassing both internal and external forms. These phenomena include the insertion of words, phrases, clauses, and baster elements. Contextual analysis of linguistic units at the word, phrase, and clause levels is essential for interpreting their communicative functions within advertisements. Overall, the results demonstrate that code-switching and code-mixing play a significant role in advertising language, functioning as effective communication strategies while contributing to the maintenance of linguistic diversity